Subclinical mastitis in crossbred dairy cows: Staphylococcus spp. and risk factors in small holder dairy farms - KARABASANAVAR, NAGAPPA; L, MANJUNATHA; S, NAVEENKUMAR G; N, JEEVAN M; SIVARAMAN, G K (The Indian Journal of Animal Sciences, 2022)
Subclinical mastitis (SCM) is one of the major economic diseases of dairy cows. In the present cross-sectionalstudy, dairy cows (n=205) of small holding dairy farms were screened using California mastitis test (CMT) andprevalence of 12.19% was recorded. Holstein Friesian and Jersey crossbred cows showed highest CMT score of 2followed by 3, 1 and T; linear scores of somatic cell counts (SCC) of 3.14±0.08, 4.72±0.25, 6.17±0.12, 7.99±0.11and 9.84±0.45 were observed for CMT scores N, T, 1, 2 and 3, respectively. Risk factors associated with SCM werestudied in 25 randomly selected cows. Staphylococcus species were detected in 54% of quarters based on PCRamplification of 16s rRNA gene; thermonuclease (nuc gene) PCR categorized Staphylococcus species as S. aureus(SA, 37%) and non-aureus Staphylococci (NAS, 26%). Significant association between CMT score 2 andStaphylococcus species was established. Staphylococcus species, SA and NAS, were detected in 30.7, 20.5 and17.9% of SCM negative as well as 68.85, 47.54 and 31.14% SCM positive quarters, respectively. Significantassociation between SCM and Staphylococcus species and Staphylococcus aureus was observed. Study indicatedstrong association between SCM, Staphylococcus aureus and certain risk factors among cows reared under smallholding dairy farms of the tropical region.